Psychological Portrait: Empirical Study of the Elderly in the Keputih Social Boarding School Environment, Surabaya - Ayong Lianawati; Veranda Yuniar Maisefa Sefa; Syifa’ul Afidah; Afaf Akiko (Ma'soem University, 2022)
Research on